Exploring the Synergy Between Neuro-Inspired Algorithms and Quantum Computing in Machine Learning - G Nithya; R, Praveen Kumar; V. Dineshbabu; P. Umamaheswari; T, Kalaivani (International Journal of Computational and Experimental Science and Engineering, 2025)
The integration of neuro-inspired algorithms and quantum computing in machine learning presents a promising frontier for addressing complex computational challenges in modern AI. Neuro-inspired algorithms, such as artificial neural networks (ANNs), deep learning (DL), and spiking neural networks (SNNs), have demonstrated impressive performance in various domains, including image recognition, natural language processing, and autonomous systems. This research explores the synergy between neuro-inspired algorithms and quantum computing, focusing on how quantum-enhanced machine learning models can accelerate training and inference processes in neuro-inspired systems. Quantum neural networks (QNNs) leverage quantum principles, such as superposition and entanglement, to represent and manipulate data in ways that classical systems cannot. By combining quantum computing’s parallelism with the flexibility and learning capability of neuro-inspired algorithms, the proposed hybrid models can provide exponential speedups in tasks involving large-scale data processing and optimization. To evaluate the performance of these hybrid models, experiments were conducted using a quantum-enhanced deep learning model applied to image classification and a neuro-inspired algorithm augmented by quantum optimization techniques for optimization tasks. The quantum-enhanced deep learning model achieved a 45% reduction in training time compared to classical deep learning models while maintaining similar accuracy levels. These findings highlight the significant potential of combining quantum computing with neuro-inspired algorithms, opening new avenues for faster, more efficient machine learning models capable of solving previously unsolvable problems. The synergy between these two domains could lead to breakthroughs in areas like artificial general intelligence (AGI), drug discovery, and autonomous systems, where large-scale optimization and pattern recognition are critical.